Javanese Fashion on the Small Screen: Sustaining Tradition through Costume in Gadis Kretek Series - Tiara Larissa; Muchammad Zaenal Al Ansory (JURNAL RUPA, 2025)
This study examines how Javanese traditional aesthetics are preserved and recontextualized through costume characters in the Gadis Kretek film series. As visual media increasingly shapes contemporary fashion discourse, film operates as a cultural agent that constructs and communicates meanings of traditional dress within specific socio-cultural contexts. In Gadis Kretek, costume design is not merely decorative but is deeply embedded in the narrative, representing Javanese women’s identities within the socio-historical context of kretek culture. The series portrays women across different social positions, from aristocratic figures to female laborers in the kretek industry, where costume becomes a key visual element in expressing class distinction, gender roles, and cultural expectations. This research employs a qualitative approach using visual semiotic analysis, focusing on denotative, connotative, and mythological meanings of costume elements. The analysis explores how visual elements such as kebaya, batik motifs, textile materials, and accessories function as cultural signs that reflect social hierarchy, femininity, labor identity, and historical context. Particular attention is given to how variations in material quality, silhouette, and styling construct contrasting representations of Javanese women. The findings show that costume characters function as cultural signifiers that articulate Javanese femininity, class distinction, and labor identity, while also reinforcing cultural narratives rooted in tradition. At the same time, the use of traditional materials and craftsmanship reflects values aligned with sustainable fashion practices, particularly in terms of cultural preservation, local knowledge transmission, and continuity of artisanal practices. This study highlights how film, through costume design, not only preserves Javanese traditional aesthetics but also actively reinterprets them within contemporary visual culture.